Pulmonary Artery Smooth Muscle Cell Senescence Promotes the Proliferation of PASMCs by Paracrine IL-6 in Hypoxia-Induced Pulmonary Hypertension - Wang, Ai-Ping; Yang, Fang; Tian, Ying; Su, Jian-Hui; Gu, Qing; Chen, Wei; Gong, Shao-Xin; Ma, Xiao-Feng; Qin, Xu-Ping; Jiang, Zhi-Sheng (Frontiers in Physiology, 2021)
Pulmonary hypertension (PH) is a critical and dangerous disease in cardiovascular system. Pulmonary vascular remodeling is an important pathophysiological mechanism for the development of pulmonary arterial hypertension. Pulmonary artery smooth muscle cells (PASMCs) proliferation, hypertrophy and enhancing secretory activity are the main causes of pulmonary vascular remodeling. Previous studies have proved that various active substances and inflammatory factors, such as Interleukin -6, Interleukin-8, Chemotactic Factor for Monocyte-1 (MCP-1), etc., are involved in pulmonary vascular remodeling in pulmonary hypertension. However, the underlying mechanism of these active substances to promote the PASMCs proliferation remain to be elucidated. In our study, we demonstrated that PASMCs senescence, as a physiopathologic mechanism, played an essential role in hypoxia-induced PASMCs proliferation. In the progression of PH, senescence PASMCs could contribute to PASMCs proliferation via increasing the expression of paracrine IL-6 (senescence-associated secretory phenotype, SASP). In addition, we found activated mTOR/S6K1 pathway can promote PASMCs senescence and elevate hypoxia-induced PASMCs proliferation. Further study revealed that the activation of mTOR/S6K1 pathway was responsible for senescence PASMCs inducing PASMCs proliferation via paracrine IL-6. Targeted inhibition of PASMCs senescence could effectively suppress PASMCs proliferation, and relieve pulmonary vascular remodeling in PH, indicating a potential for the exploration of novel anti-pulmonary hypertension strategies.